THE ROLE AND ROLE OF SOCIAL SOCIETY PRINCIPLES IN SOCIETY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes the place and role of the principles of social cohesion in the life of the society specific to the social sphere. In this case, a comparative analysis of the scientific and practical experience of developed countries. It was stated that social solidarity is a sociological interpretation of interests, goals, interests and mutual understanding, and the problem of ensuring the stability of human rights and freedoms was put forward.